TINJAUAN PELAKSANAAN ASSEMBLING DALAM PENGENDALIAN KELENGKAPAN REKAM MEDIS UNTUK PENINGKATAN MUTU PELAYANAN DI RSUD PONDOK AREN - Lestari, Santi; Rahmi, Junaida; Rusdiana, Ima; Berliana, Azzahra; Kuntoadi, Gama Bagus (EDU RMIK Jurnal Edukasi Rekam Medis Ilmu Kesehatan, 2026)
Medical records are important documents that support the quality of health services, administration, and legal protection in hospitals. One of the important processes in medical record management is assembling, which is the process of collecting, arranging, and reviewing the completeness of medical record documents. This study aims to review the implementation of assembling in controlling the completeness of medical records to improve service quality at Pondok Aren Regional General Hospital.This research used a quantitative descriptive design with purposive sampling. The sample consisted of 127 inpatient medical record files. Data were collected through observation sheets, documentation studies, and interviews with three medical record officers involved in the assembling process.The results showed that the completeness of patient identity such as patient name, gender, and medical record number reached 100%. However, several components were still incomplete, including admission and discharge forms (79%) and medical resume (73%). In addition, the implementation of assembling had not been fully optimal due to limitations in human resources and the still manual medical record system.The study concludes that the implementation of assembling in controlling the completeness of medical records at Pondok Aren Regional General Hospital still needs improvement. Hospitals are expected to conduct periodic evaluations and prepare for the transition to electronic medical record systems to improve the quality of medical record management.